Ubiquitin chain topology in plant cell signaling: a new facet to an evergreen story - Walsh, Charlotte K.; Sadanandom, Ari (Frontiers in Plant Science, 2014)
Ubiquitin is a peptide modifier able to form polymers of varying length and linkage as part of a powerful signalling system. Perhaps the best-known aspect of this protein’s function is as the driver of targeted protein degradation through the Ubiquitin Proteasome System (UPS). Through the formation of lysine 48-linked polyubiquitin chains, it is able to direct the degradation of tagged proteins by the 26S proteasome, indirectly controlling many processes within the cell. However, recent research has indicated that ubiquitin performs a multitude of other roles within the cell beyond protein degradation. It is able to form 6 other ‘atypical’ linkages though lysine residues at positions 6, 11, 27, 29, 33 and 63. These atypical chains perform a range of diverse functions, including the regulation of iron uptake in response to perceived deficiency, repair of double stranded breaks in the DNA, and regulation of the auxin response through the non-proteasomal degradation of auxin efflux carrier protein PIN1. This review explores the role ubiquitin chain topology plays in plant cellular function. We aim to highlight the importance of these varying functions and the future challenges to be encountered within this field.